IMPROVING THE EFFECTIVENESS OF TEACHING INFORMATICS IN THE DIGITAL LEARNING ENVIRONMENT - Doniyor Abdurakhimov (Journals Park Publishing, 2025)
In the modern era of digital transformation, the discipline of Informatics has evolved from a technical subject into a key driver of cognitive, creative, and socio-technological competence. This research examines the pedagogical strategies, technological frameworks, and methodological innovations required to improve the effectiveness of teaching Informatics in a digital learning environment. Using an integrative theoretical and analytical approach, the study explores the alignment between digital pedagogy, computational thinking, and learner autonomy, highlighting the essential role of adaptive technologies, gamification, artificial intelligence (AI) tools, and blended learning models in enhancing educational outcomes. The article also analyzes empirical data and global educational models to identify the most efficient digital strategies for engaging learners in Informatics, emphasizing teacher competence, digital literacy, and innovative assessment methods. The findings indicate that the optimization of Informatics education depends on three interrelated factors: the integration of digital platforms with curriculum goals, the professional development of teachers in ICT-based pedagogy, and the creation of interactive learning environments that foster collaboration and problem-solving. This study contributes to the theoretical foundations and practical applications of digital pedagogy, offering an evidence-based model for increasing instructional efficiency in Informatics education across different educational levels.
Keywords: Digital learning, Informatics education, teaching effectiveness, ICT integration, computational thinking, digital pedagogy, e-learning, blended education.